Use function notation to write a recursive formula to represent the sequence: 4, 8, 12, …
1 answer:
Answer:
- f(1) = 4
- f(n) = f(n - 1) + 4
Step-by-step explanation:
Given the sequence:
The first term is 4 and common difference is 4
<u>Recursive formula:</u>
- f(1) = 4
- f(n) = f(n - 1) + 4
You might be interested in
12w - 13 - 11w + 24 = 77
combine like terms
w + 11 = 77
subtract 11 from both sides
w = 66
Answer:
380.13
Step-by-step explanation:
hope this helps :D pls mark brainliest :D
Answer:
Step-by-step explanation:
ok put them in the order i say them
true
true
false
true
false
16x34=544 rats the answer hope this would help